2015
DOI: 10.4293/jsls.2015.00023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Subcutaneous and Visceral Fat After Gastric Balloon Treatment

Abstract: Background and Objectives:This project is a continuation of a larger project entitled “Treatment with intragastric balloon (IGB) in patients with overweight and obesity in Recife” developed by Professor Dr. Gustavo Lopes de Carvalho. It is a project studying the effectiveness of treatment with IGB evaluating the loss of weight and body mass index and its impact on blood pressure, blood glucose, triglycerides, total cholesterol and fractions. It also assesses the lifestyle of patients studying whether treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…This area is anatomically well defined and insensitive against respiratory and digestive organ movement. According to our data, a loss of visceral and subcutaneous fat was described by Cabral in 25 patients via ultrasound [ 32 ]. We could not find a measurement of retroperitoneal fat in the literature during gastric balloon therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This area is anatomically well defined and insensitive against respiratory and digestive organ movement. According to our data, a loss of visceral and subcutaneous fat was described by Cabral in 25 patients via ultrasound [ 32 ]. We could not find a measurement of retroperitoneal fat in the literature during gastric balloon therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the restrictive effect of the balloon may provide a positive reinforcement that persists beyond removal, with early satiety and weight loss promoting continued behavioral change 27 and with improved lung function, metabolic parameters, and body fat distribution. 31 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that there was a significant reduction of visceral fat area 6,34 , while other authors reported that the visceral fat area showed no significant decrease 33 .…”
Section: /7mentioning
confidence: 99%